Two Sources of Maternal Iodine Intake and Their Effect on Maternal and Infant Iodine Status and Thyroid Function and Infant Information Processing in Southern Ethiopia (P11-007-19). (13th June 2019) - Gebreegziabher, Tafere; Stoecker, Barbara
Abstract: Objectives: The objective of this study was to assess the effects of two sources of iodine supplementation on maternal and infant thyroid function and on visual information processing (VIP) of infants in southern Ethiopia Methods: A community-based, randomized, supplementation trial was conducted. Mother infant dyads (n = 106) were recruited within the first week after delivery to participate in this study. Mothers were randomly assigned either to receive a potassium iodide capsule (225 µg iodine) daily for 26 weeks or appropriately iodized salt weekly for 26 weeks for household consumption. Maternal thyroxine (T4 ), triiodothyronine (T3 ), thyroid stimulating hormone (TSH), thyroglobulin (Tg), urinary iodine concentration (UIC), breast milk iodine concentration (BMIC) and infant T4, TSH, UIC and VIP were measured as outcome variables. Results: At baseline, neither mothers nor infants in the two groups (capsule and iodized salt groups) were significantly different in any of the biomarkers and anthropometry measurements. Maternal TSH and goiter rate significantly decreased following iodine supplementation but T3, T4 and Tg didn't change. Maternal UIC and BMIC and infant UIC were not different among groups. Conclusions: A maternal dose of 225 µg iodine daily or adequately iodized salt initiated within a week after delivery decreased goiter and TSH but did not impact infant T4, TSH or VIP. The two treatment groups didn't differ in any of the outcome variables. Funding Sources: The study was funded by Nestlé Foundation and Oklahoma State University.